The Critical Role of Imaging in Primary Progressive Multiple Sclerosis - Yueniwati, Yuyun; Inggrianita, Dotti (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Multiple sclerosis (MS) is an autoimmune-related neurological disorder as a result of chronic inflammation and demyelination which affect the central nervous system. The number of MS cases in Indonesia is about 1–5/100.000 people. This disease causes disability and requires immense treatment costs. One of the MS subtypes is primary progressive which is marked by the decline of neurological functions since the disease onset, without any period of relapse attacks. CASE REPORT: A 59-year-old female came with complaints on spinning dizziness, accompanied by vomiting and waddling for the past month before hospital administration. Based on physical examination, we found multiple cranial nerve palsies on the cranial nerve III, IV, V, VI, and VII on the left side. Initially, it suspected as an intracranial lesion in the cerebellopontine angle. However, brain computed tomography scan showed a normal result. Brain magnetic resonance imaging (MRI) was conducted and we found multiple lesions on the supratentorial and infratentorial region. The second patient was a 24-year-old female complained about waddling gait for the past year, which grew heavier. Based on physical examination, we found a cerebellar sign on the left side, cerebellar ataxia, paraparesis of lower extremity, and paresthesia. Brain MRI with contrast displayed white matter periventricular and infratentorial lesion. CONCLUSION: In both cases, radiological imaging examination, which was MRI with contrast, was beneficial in the establishment of patient’s diagnosis, which made therapeutic management suitable as needed.